Historical philosophical analysis of women's rights legislation compared to Islamic legislation - Ejlal Ali Mohammed AlMAKHATHI (Social Empowerment Journal, 2024)
Women were still the focus of attention of researchers and thinkers, as they are the main actor in society, they are not part as much as they are all that create generations and manage houses, infiltrated many concepts that seek to clarify the right of women and branched until they stood before a challenge to answer him Did the woman really take her right?, In this study that is concerned with the historical aspect of the development of views, in turn interested in women as well to achieve theoretical goals for concepts that concern women's rights.